Needs Assessment As A Basis For Development Of 2013 Curriculum Content In English - Nanik Supriani; Imam Ghozali; Teguh Bangkit Pamungkas (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
The present research is aimed at finding out whether (a) it is necessary to include lexico-grammatical features in curriculum content especially the basic competences (KD) for each level of student education as perceived by English teachers, and (b) what lexico-grammatical features are needed by junior high school students to be included. The present study was conducted based on principles of qualitative research involving four senior English teachers with various expertise; 1 regional and involving national test designer, and one expert of curriculum working for the ministry of Education. The finding were; (a) All teacher participants stated that special lists of lexico-grammatical features are needed to be included in the curriculum to serve as guidance to develop teaching materials and also a reference for regional and national test designers in developing regional or national examination. However, students are still encouraged to find more English words for their own needs. (b) Lexico-grammatical features to be included in the curriculum should be presented in thematic classification and classified in verbs, adjectives and nouns. Further, the lists are sequenced from simple to complex and based of frequency of occurrence. The lists should also be classified into different grades; the 7th, 8th and 9th grades.